2020
DOI: 10.1177/1060028020959039
|View full text |Cite
|
Sign up to set email alerts
|

Initial Dosage Optimization of Tacrolimus in Pediatric Patients With Thalassemia Major Undergoing Hematopoietic Stem Cell Transplantation Based on Population Pharmacokinetics

Abstract: Background: Hematopoietic stem cell transplantation (HSCT) is an effective treatment for hematological disorders. Tacrolimus is widely used after HSCT, but it has highly interindividual variable pharmacokinetics. Population pharmacokinetics (PPK) researches of tacrolimus in children with β-thalassemia major (β-TM) undergoing HSCT are insufficient. Objective: To establish a PPK model of tacrolimus in children with β-TM and optimize initial dosing regimen for achieving target concentration of 5 to 15 ng/mL. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Tacrolimus is a first-line agent for GVHD prevention and has been routinely employed to stop rejection of HSCT [15][16][17][18]. However, tacrolimus has a narrow therapeutic range; the use of high concentrations seems to be related to toxicity, while lower concentrations are related to an acute rejection's increased risk (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus is a first-line agent for GVHD prevention and has been routinely employed to stop rejection of HSCT [15][16][17][18]. However, tacrolimus has a narrow therapeutic range; the use of high concentrations seems to be related to toxicity, while lower concentrations are related to an acute rejection's increased risk (23).…”
Section: Discussionmentioning
confidence: 99%
“…HSCT may adjust superoxide generation, making neutrophil function within normal range and improvement in inflammatory progression (14). However, HSCT patients must take tacrolimus, a potent immunosuppressant, for a prolonged period to prevent transplant rejection (15)(16)(17)(18). In addition, voriconazole, a second-generation triazole with potent broad-spectrum antifungal activity, is used for prophylaxis against invasive fungal disease (IFD), which is a major cause of morbidity and mortality in pediatric patients after HSCT (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HSCT significantly improves the quality of life of CD patients, and 50% of CD patients who underwent HSCT achieved complete healing of the mucosa and clinical remission ( Lindsay et al, 2017 ; Lopez-Garcia et al, 2017 ; Ruiz et al, 2020 ). However, for HSCT patients, long-term tacrolimus treatment is necessary to prevent rejection ( Gao and Ma, 2019 ; Ishiwata et al, 2020 ; Soskind et al, 2020 ; Zhou et al, 2020 ). Similarly, posaconazole is also needed for the prevention of invasive fungal disease (IFD) in HSCT patients ( Busca et al, 2016 ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tacrolimus PK variability is particularly important to consider in the pediatric population given the differences in absorption, distribution, metabolism and excretion among children of various sizes and at different stages of development ( Kearns et al, 2003 ). Given the known variability in PK of tacrolimus in pediatric patients, several recently published studies have described pediatric-specific population pharmacokinetic (PopPK) models along with their associated dosing guides ( Wallin et al, 2009 ; Andrews et al, 2018 ; Wang et al, 2020 ; Zhou et al, 2021 ). Zhou et al developed a model within a subpopulation of children undergoing HCT for β-thalassemia ( Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the known variability in PK of tacrolimus in pediatric patients, several recently published studies have described pediatric-specific population pharmacokinetic (PopPK) models along with their associated dosing guides ( Wallin et al, 2009 ; Andrews et al, 2018 ; Wang et al, 2020 ; Zhou et al, 2021 ). Zhou et al developed a model within a subpopulation of children undergoing HCT for β-thalassemia ( Zhou et al, 2021 ). Wang et al and Wallin et al described similar models where a one-compartment model best described the dataset and allometrically scaled weight improved approximations of clearance (Cl) and volume of distribution (Vd) ( Wallin et al, 2009 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%